The Determinants of Adult Education and Training Participation in the US: A Machine Learning Approach - Chang Sung Jang; Junghwa Choi; Romit Maulik; Doo Hun Lim (Adult Education Research Conference, 2022)
This study aims to explore the determinants of adult education and training (AET) participation of working adults. Through random forest analysis, we discovered important factors contributing to AET participation.
Keywords: adult education and training participation; working adults; machine learning; PIAAC